Factors Associated With Medication Adherence Among Medical-Aid Beneficiaries With Hypertension. (October 2016) - Ahn, Yang Heui; Ham, Ok Kyung
The purpose was to examine factors associated with medication adherence among medical-aid beneficiaries with hypertension using the Expanded Behavioral Model of Health Services Utilization. A cross-sectional study was conducted with a convenient sample of 289 patients. The instruments included scales to measure medication adherence, health literacy, general self-efficacy, and pros and cons of chronic disease management. Data collection was performed between February and March 2011. A hierarchical regression analysis was performed. The study found that 25.6% to 34.6% had low motivation and low knowledge regarding medication adherence. Those with higher health literacy and higher self-efficacy scores were more likely to have higher medication adherence, whereas widowed and those who perceived more cons of chronic disease management were more likely to have lower medication adherence than their counterparts ( p < .05). Interventions incorporating significant factors associated with medication adherence are required to enhance medication adherence and to prevent complications associated with medication non-adherence.